Effects of ankle destabilization devices and rehabilitation on gait biomechanics in chronic ankle instability patients: A randomized controlled trial. (September 2016) - Donovan, Luke; Hart, Joseph M.; Saliba, Susan; Park, Joseph; Feger, Mark A.; Herb, C. Collin; Hertel, Jay
Abstract: Patients with chronic ankle instability (CAI) have altered gait patterns, which are characterized by increased inversion positioning during gait. Ankle destabilization devices increase peroneus longus muscle activation during gait, which may increase eversion. Objective: To determine whether incorporating destabilization devices into a 4-week impairment-based rehabilitation program has beneficial effects on gait biomechanics and surface electromyography (sEMG) compared to impairment-based rehabilitation without destabilization devices in CAI patients. Design: Randomized controlled trial. Setting: Laboratory. Participants: Twenty-six CAI patients. Outcome measures: Patients completed baseline gait trials and were randomized into no device or device groups. Groups completed 4-weeks of rehabilitation with or without devices, and then completed post-intervention gait trials. Lower extremity sagittal and frontal plane kinematics and kinetics and sEMG activity were measured. Results: The device group increased dorsiflexion during mid-late stance and had lower normalized sEMG amplitude for the peroneus longus during early stance and mid-swing after rehabilitation. The no device group had less peroneus brevis sEMG activity during early stance after rehabilitation. Conclusion: Incorporating destabilization devices in a 4-week rehabilitation program was an effective method of improving dorsiflexion during the stance phase of gait. However, impairment-based rehabilitation, regardless of instability tool, was not effective at improving frontal plane motion. Highlights: Ankle destabilization devices may improve dorsiflexion during gait. Impairment-based rehabilitation does not improve frontal plane kinematics or kinetics. Impairment-based rehabilitation programs should include specific gait training interventions.